Down regulation of serum protein expression in oral submucous fibrosis: A proteomic study - Nimi Susan Mathew; Prashanth Shenoy; Laxmikanth Chatra; K M Veena; Rachana V Prabhu; Tashika Kuttappa (Wolters Kluwer Medknow Publications, 2018)
Background: Oral submucous fibrosis (OSMF) is a potentially malignant condition, which affects the oral cavity and the oropharynx. Despite the high prevalence rates of the disease and the morbidity and mortality related to the malignant transformation of 3%-19%, that is, OSMF into oral squamous cell carcinoma, there are fewer methods to identify the malignant transformation associated with OSMF. Dissecting the molecular aspects of these disorders will significantly contribute to improved prevention, early diagnosis, and clinical management. The complementary process involved in decreasing of the cellular components is called downregulation and the vice versa is known as upregulation. Materials and Methods: To predict the malignant transformation of OSMF, a study was conducted for quantitative proteomic profiling on the serum of histopathologically proven patients with OSMF to identify the candidate protein biomarkers. Among the differentially expressed proteins, only the downregulated proteins are included in the scope of this article. Results: During the study, 133 proteins were identified from the plasma of the case samples who histopathologically confirmed OSMF. These proteins were identified using mass spectrometric analysis. During the analysis, 14 proteins were differentially expressed. A fold change of more than 1.5 indicates upregulated proteins and less than 0.6 indicates downregulated proteins when compared with the control group. Conclusion: This study depicts the scope of the candidate protein biomarkers that can aid in definitive diagnosis of OSMF through a minimally invasive technique and help in the early detection and better treatment planning to reduce the morbidity of the disease in the future.